2004
DOI: 10.1128/iai.72.4.2312-2320.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role for Moesin in Lipopolysaccharide-Stimulated Signal Transduction

Abstract: Moesin is a 78-kDa protein with diverse functions in linking the cytoskeleton to the membrane while controlling cell shape, adhesion, locomotion, and signaling. The aim of this study was to characterize the expression and localization of moesin in mononuclear phagocytes by using confocal microscopy, flow cytometry, immunoprecipitation, and Western blotting and to analyze the function of moesin as a lipopolysaccharide receptor, utilizing an antisense oligonucleotide approach to knock down the moesin gene. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
3
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 55 publications
(44 reference statements)
1
46
3
5
Order By: Relevance
“…5). (Iontcheva et al, 2004). 이 중 NO 형성은 박테리아를 죽이 거나 종양을 제거시키는 중요한 역할을 하지만, 병리적인 원 인에 의한 과도한 NO 형성은 염증을 유발시키게 되며 조직의 손상, 유전자 변이 및 신경 손상 등을 유발한다 (Stuehr et al, 1991;McCartney-Francis et al, 1993;Weisz et al, 1996).…”
Section: 뚝새풀 추출물(Ds)이 Raw 2647에서 Lps로 유도된 P-iκbα 발현에 미치는 영향unclassified
“…5). (Iontcheva et al, 2004). 이 중 NO 형성은 박테리아를 죽이 거나 종양을 제거시키는 중요한 역할을 하지만, 병리적인 원 인에 의한 과도한 NO 형성은 염증을 유발시키게 되며 조직의 손상, 유전자 변이 및 신경 손상 등을 유발한다 (Stuehr et al, 1991;McCartney-Francis et al, 1993;Weisz et al, 1996).…”
Section: 뚝새풀 추출물(Ds)이 Raw 2647에서 Lps로 유도된 P-iκbα 발현에 미치는 영향unclassified
“…However, for most of these proteins, a functional participation in signal transduction is not clear, yet. For other molecules, such as MOESIN (24,25) and mLBP (26), a functional participation in cell activation by LPS has been shown. Several publications including our own have reported that potassium channels are involved in the activation of monocytes, macrophages, and endothelial cells by LPS (27)(28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%
“…Following activation, macrophages modulate the expression of accessory molecules such as CD14 and toll-like receptor (TLR) 4. 4,5) Stimulation of TLR4 by lipopolysaccharide (LPS) triggers the recruitment of the cytoplasmic adaptor protein MyD88 and subsequently culminates in the activation of downstream signaling pathways: the transcription factor nuclear factor-kB (NF-kB) pathway. These pathways induce the expression of various inflammatory mediators, including nitric oxide (NO), prostaglandins (PGs), and inflammatory cytokines.…”
mentioning
confidence: 99%